THE RELATIONSHIP OF AUDIT COMMITTEE AND COMPANY VALUE ADDED PERFORMANCE - Soewignyo, Fanny (JBE (Journal of Business and Economics), 2013)
The purpose of this study is to examine the relationship of audit committee characteristics and company value added performance in the property, real estate, and building construction companies listed on Indonesia Stock Exchange in 2011.  The study employs four characteristics of audit committee (audit committee size, frequency of  audit committee meetings, number of independent commissioners in audit committee, and financial or accounting expert in audit committee) as independent variables and intellectual capital efficiency using The Pulic’s Value Added Intellectual Coefficient method has been employed to measure the company value added performance as dependent variable.  The result suggests that the overall model is not significant.  Furthermore, turning to the significance of each independent variable, the t-statistic and p-value suggest that all the coefficients for audit committee characteristics are not significant at the 5% level.  The result of the study reveals that the establishment of audit committee is not an important driver of intellectual capital efficiency in the context of property, real estate, and building construction industry in Indonesia.